Consulta nutricional personalizada online - Díaz De Valencia, Margarita Isabel (2016)
This business project has been conducted in order to investigate the feasibility of starting and entry into the market of NUTRIENNDO, a company aimed at providing nutritional consultation Online to customers of socioeconomic segments A and B concerned about their welfare and interested in satisfying their healthy eating needs. Our promise of value is given by distance education, personalized treatment, supported by using social networks and empowering the client to learn to choose healthy and consciously best for him and his family; in a timely, fast and quality manner by highly qualified staff. NUTRIENNDO is originated in Lima - Peru and directs his attention to the Peruvian customer who for reasons of time and distance do not have access to specialized nutritional care and to foreign Spanish-speaking customers that for reasons of cost, lack of insurance or language required to have a close counseling, friendly and who share their habits regarding food. Changes in lifestyle in an environment that encourages healthy living made possible the creation of NUTRIENNDO, the latest technology in telecommunications and the internet in Peru grows and increasingly modern mobile devices that help and allow its connection with the rest of the world. "NUTRIENNDO" has a process of well structured attention and will have the latest technological support to deliver our promise of value during and after the respective attention. We will use intense social marketing media that allows the positioning of the brand, as well as social and virtual networks that will allow continued interaction between users and the company. In order to determine the financial viability of the project, we calculated an initial investment of $.12,165 and with our own capital. With a financial cash flow for the first 3 years. As seen in detail in the appropriate chapter. The result of the projection shows a profitable and self-sustaining operation with attractive investment returns, given the absence of significant fixed costs in the cost structure (benefit of “online” model).